Adult-Onset Encephalitis over Twelve Years in Easternmost Finland - Sipilä (S. Karger AG, 2026)
Introduction: The epidemiology of encephalitis varies by region and time. Available Finnish data are outdated and there are no data from eastern parts of the country nor concerning the occurrence of autoimmune encephalitides. Materials and Methods: Patients with encephalitis were identified from mandatory administrative registries in North Karelia Central Hospital. The diagnoses were verified and data extracted by reviewing the patient records. Study period was 2010-2021. Only patients >16 years of age were included. Results: Fifty-one patients with a clinical encephalitis were identified (55% men) with a median age of 65 years (interquartile range 45, 73; total age range 16-88 years) indicating a crude incidence of 3.1/100,000 personyears for the entire study period. A specific aetiology could be identified in 31 cases (61%) with tick-borne encephalitis (TBE) being the most common one (20% of all 51 cases), followed by herpes simplex virus type 1 (HSV-1, 16%) and varicella zoster virus (VZV, 14%). Autoimmune aetiology was confirmed in 10%. TBE was most often found in the youngest age group (16-52 years of age) and the herpes viruses in the oldest group (71 years or older). A specific cause was most often identified in the oldest patients (78%). TBE patients were younger than patients with VZV (p = 0.0009) or HSV-1 (p = 0.0057), but there was no difference when they were compared to patients with autoimmune (p = 0.27) or unknown (p = 0.074) aetiology. At presentation, there were differences in the occurrence of some clinical signs and symptoms between aetiologies but nothing specific. Eight patients (16%) were immunosuppressed. Inpatient seizures occurred in 10 patients (20%). In these cases, the aetiology was HSV-1 in 50% and TBE or VZV in none. A full recovery was observed in 51% of all patients while 3 patients (6%) had died of the encephalitis while in hospital or shortly after discharge. Conclusions: Adult-onset encephalitis was more common and the patients older in easternmost Finland than previously reported in other parts of the country. TBE, HSV-1, and VZV are the most commonly identified specific aetiologies whereas a fifth of the cases are probably caused by autoimmunity. Prognosis depended on aetiology but was very good in the majority of cases.